2020
DOI: 10.21873/invivo.12030
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Admission in Critical Care Units Following Gynecologic Oncology Surgery: Outcomes Based on a Systematic Review and Authors' Recommendations

Abstract: Background/Aim: The present study aimed to evaluate the predictors of admission to the Critical Care Units (CCUs) and factors predisposing to prolonged stay in CCUs after gynecological oncology surgery. Patients and Methods: Studies which addressed cases of women who underwent surgery for gynecological malignancies and required postoperative CCU admission were included. Results: Seven studies with 3820 patients were included. Among them, 1680 required admission to CCU. Advanced age, higher Charlson Comorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(74 reference statements)
0
1
0
1
Order By: Relevance
“…In addition, cancer patients undergoing potentially curative therapy and even those with an advanced form of the disease, but with a chance of long-term survival, can benefit from ICU admission (30). Some studies have found that the reasons why cancer patients are admitted to the ICU are age (elderly), operating time, bleeding, intestinal resection, hospital readmissions and low survival rates, hemodynamic instability, and fluid management (31), advanced-stage cancer, emergencies, sepsis/septic shock, respiratory failure (32), being male, of mixed race, married, post-surgical, hypertensive, diabetic, and with pulmonary comorbidities (33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer patients undergoing potentially curative therapy and even those with an advanced form of the disease, but with a chance of long-term survival, can benefit from ICU admission (30). Some studies have found that the reasons why cancer patients are admitted to the ICU are age (elderly), operating time, bleeding, intestinal resection, hospital readmissions and low survival rates, hemodynamic instability, and fluid management (31), advanced-stage cancer, emergencies, sepsis/septic shock, respiratory failure (32), being male, of mixed race, married, post-surgical, hypertensive, diabetic, and with pulmonary comorbidities (33).…”
Section: Discussionmentioning
confidence: 99%
“…Cerrahi ve anestezi işlemleri ve postoperatif yoğun bakım takiplerindeki gelişmeler sonrasında; jinekolojik kanser nedenli operasyonlara bağlı mortalite ve komplikasyonların sıklığında azalma görülmüştür. Postoperatif dönemde rutin yoğun bakım takibi, özellikle evreleme cerrahisi yapılan ve operasyon süresi uzun olan ileri evre over ve endometrium kanserinde gerekli görülmektedir (2).…”
unclassified